Tear osmolarity and ocular surface parameters in patients with psoriasis - Demirci, Göktuğ; Karaman Erdur, Sevil; Aydın, Rukiye; Balevi, Ali; Eliaçık, Mustafa; Özsütçü, Mustafa; Olmuşçelik, Oktay (Conselho Brasileiro de Oftalmologia, 2017)
Purpose: The aim of this study was to evaluate tear osmolarity, tear film function, and ocular surface changes in patients with psoriasis. Methods: At a single center, 30 eyes of 30 patients with psoriasis (group 1) and 30 eyes of 30 healthy individuals (group 2) were evaluated using the Ocular Surface Disease Index (OSDI) questionnaire, Schirmer I test, tear film break-up time (TBUT) test, scoring of ocular surface fluorescein staining using a modified Oxford scale, and tear osmolarity measurement. Results: Tear osmolarity values, OSDI, and Oxford scale scores were significantly higher in group 1 (309.8 ± 9.4 mOsm, 38.9 ± 1.1, and 0.7 ± 1.1, respectively) than in group 2 (292.7 ± 7.7 mOsm, 4.2 ± 0.3, and 0.1 ± 0.3, respectively; p<0.01 for all). TBUT was significantly lower in group 1 (8.7 ± 3.6 s) than in group 2 (18.1 ± 2.8 s; p<0.001). No significant differences were detected in Schirmer I test values between the groups (16.2 ± 2.5 mm in group 1 and 16.6 ± 2.3 mm in group 2; p=0.629). Conclusions: The results of this study showed that psoriasis may influence tear osmolarity and tear film function. Patients with psoriasis showed tear hyperos-molarity and tear film dysfunction.

Objetivo: O objetivo deste estudo foi avaliar a osmolaridade da lágrima, função do filme lacrimal e alterações da superfície ocular em pacientes com psoríase. Método: Em um único centro, 30 olhos de 30 pacientes com psoríase (grupo 1) e 30 olhos de 30 indivíduos saudáveis (grupo 2) foram avaliados pelo questionário do Índice de Doença da Superfície Ocular (OSDI), teste de Schirmer tipo I, tempo de ruptura do filme lacrimal (TBUT), coloração por fluoresceína da superfície ocular utilizando a escala de Oxford modificada e osmolaridade lacrimal. Resultados: Os valores de osmolaridade lacrimal, OSDI e escores da escala de Oxford foram significativamente maiores no grupo 1 (309,8 ± 9,4 mOsm, 38,9 ± 1,1 e 0,7 ± 1,1, respectivamente) em comparação com o grupo 2 (292,7 ± 7,7 mOsm, 4,2 ± 0,3 e 0,1 ± 0,3, respectivamente) (p<0,01 para todos). TBUT no grupo 1 (8,7 ± 3,6 s) foi significativamente menor em comparação com o grupo 2 (18,1 ± 2,8 s) (p<0,001). Não foram detectadas diferenças significativas nos valores de teste de Schirmer (16,2 ± 2,5 mm no grupo 1 e 16,6 ± 2,3 mm no grupo 2, p=0,629). Conclusões: Este estudo mostrou que a psoríase pode influenciar osmolaridade lágrima e função do filme lacrimal. Os pacientes com psoríase apresentaram hiperosmolaridade lágrima e disfunção do filme lacrimal.
Parâmetros de osmolaridade lacrimal e da superficie ocular em pacientes com psoríase
Keywords: Dry Eye Syndromes; Osmolar; Psoriasis; Tear Film; Tears; Síndromes Do Olho Seco; Lágrima; Concentração Osmolar; Psoríase; Fil Me Lacrimal